Exploring interval valued scales: A comparison of scale attributes between interval valued and semantic differential scales - Themistocleous, Christos; Pagiaslis, Anastasios; Smith, Andrew; Wagner, Christian (My University, 2017)
This paper explores Interval-Valued Scales (IVS) in a marketing research context and provides comparative results of an exploratory study between IVS and Semantic Differential Scales (SDS) comparing the scales using Preston and Colman’s (2000) scale attributes: i) Ease of use, ii) Speed of use, iii) Ability to precisely record desired answers, iv) Adequate expression of exact thoughts and feelings, v) Certainty/Uncertainty with personal answers and vi) Overall satisfaction with each scale.
Keywords: Marketing Management, Management; Response Measurement Scales; Survey Design; Methodological contributions